1997
DOI: 10.1182/blood.v90.7.2757
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Signaling Events in CD77-Mediated Apoptosis of Burkitt's Lymphoma Cells

Abstract: In the hematopoietic system CD77, a glycolipid surface antigen, is restricted to group I Burkitt's lymphoma (BL) cell lines and a subset of germinal center B lymphocytes. Recently, we have reported that recombinant B subunits of Verotoxin, which specifically binds to CD77, induce programmed cell death of CD77+ BL cells. Here, we show that an anti-CD77 monoclonal antibody (38.13) immobilized on tissue culture dishes also induces apoptosis, and we have explored the signal transducing events leading to this cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Ceramide quantification used a diacylglycerol (DAG) kinase assay as mentioned earlier (Taga et al, 1997). Cells were extracted using methanol:chloroform:1 N HCl (100:100:1, v/v/v).…”
Section: Determination Of Lung Ceramide Levels By Diacylglycerol Kinamentioning
confidence: 99%
“…Ceramide quantification used a diacylglycerol (DAG) kinase assay as mentioned earlier (Taga et al, 1997). Cells were extracted using methanol:chloroform:1 N HCl (100:100:1, v/v/v).…”
Section: Determination Of Lung Ceramide Levels By Diacylglycerol Kinamentioning
confidence: 99%
“…At high concentration, the B subunit of Verotoxin-1 is sufficient for driving programmed cell death in BL lines [19]. Crosslinking CD77 with immobilized 38.13 mAb has revealed that the resulting apoptosis is both Ca 2+ dependent and accompanied by the production of ceramide [20]. These observations have prompted the suggestion that CD77 may be contributing to the regulation of apoptosis in GC B cell populations [21].…”
Section: Introductionmentioning
confidence: 99%
“…Slight reduction of absorbance in the case of DM/STx(À), compared with PBS control, may indicate that the amounts of cellular proteins could be affected by STxB or other toxic factor(s) remaining in the OMVs. As previous reports have shown that STxB alone can be apoptotic in the cell line expressing higher levels of Gb3 (Taga et al, 1997;Marcato et al, 2002), it seems that the STxB pentamers of the DM/STx(À) OMVs (b) (a) Fig. 3.…”
Section: In Vitro Assay Of Omv Toxicitymentioning
confidence: 81%